FACILITATING MATHEMATICAL UNDERSTANDING IN THREE-DIMENSIONAL GEOMETRY USING THE SOLO TAXONOMY - Eyus Sudihartinih (Universitas Brawijaya, 2019)
This study aims to examine: (1) an increase in mathematical understanding of students whose learning with SOLO taxonomy of Superitem techniques compared to conventional learning, (2) completeness of mathematical understanding of students using SOLO taxonomy of Superitem techniques, (3) student attitudes toward learning using the SOLO taxonomy of Superitem techniques. The study was a quasi-experimental study in one of the high schools in Bandung with a research design control group design posttest. The population is all class X high school students. The sample was taken by the Purposive Random Sampling technique as much as two classes. Data collection is done by giving tests and non-tests. The written test is mathematical understanding in the concept of three dimensional geometry. Non tests are attitude questionnaires with a Likert scale. The results showed (1) an increase in mathematical of students whose learning using SOLO taxonomy with Superitem techniques was higher than that of students with conventional learning methods, (2) classical mastery learning in experimental classes was achieved, and (3) positive student attitudes in all indicator.